2011
DOI: 10.4039/n11-025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gypsy moth establishment and dominance in native caterpillar communities of northern oak forests

Abstract: Little research has addressed the impacts of invasive-species establishment on native forest insect communities. Such information is lacking even for gypsy moth, Lymantria dispar (L.) (Lepidoptera: Erebidae), the most thoroughly studied invasive forest insect. We investigated the ecological impacts of gypsy moth on native species at sites in north-central Ontario, Canada, with and without significant histories of gypsy moth defoliation over a 2-year period. Patterns in native forest caterpillar communities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 98 publications
(181 reference statements)
1
16
0
Order By: Relevance
“…Variation in host plant phenology has been proposed to affect herbivore performance and the potential for insect outbreaks (Falk et al, ; Jepsen et al, ; Pureswaran et al, ), and insect outbreaks in turn to modify the structure of herbivore communities (Roslin & Roland, ; Timms & Smith, ). In our study system consisting of Q. robur and a subset of its herbivore community, we found that spring phenology of the host plant had a large impact on infestation by the outbreak species A. brongniardellus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in host plant phenology has been proposed to affect herbivore performance and the potential for insect outbreaks (Falk et al, ; Jepsen et al, ; Pureswaran et al, ), and insect outbreaks in turn to modify the structure of herbivore communities (Roslin & Roland, ; Timms & Smith, ). In our study system consisting of Q. robur and a subset of its herbivore community, we found that spring phenology of the host plant had a large impact on infestation by the outbreak species A. brongniardellus .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of plantā€induced responses, previous studies have demonstrated that insect herbivores feeding on different parts of the same plant individual can have a negative affect each other's fitness (Tack, Ovaskainen, Harrison, & Roslin, ), and that insect herbivores colonizing a plant in one year could have both a negative and positive effect on colonization by herbivores in the following year (Tack et al, ). Similarly, insect herbivores colonizing a plant early in the season could affect the performance of species colonizing the plant later in the season (Van Zandt & Agrawal, ) and thereby alter the structure of the insect community (Roslin & Roland, ; Stam, Dicke, & Poelman, ; Timms & Smith, ; Van Zandt & Agrawal, ). Hence, the appearance of an earlyā€season outbreak species could have a major ecological impact on the plantā€associated food web.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray et al (2008) recorded 32% parasitism by C. concinnata in one year among gypsy moths that had recently invaded Wisconsin (USA). In another Wisconsin study, Hajek and Tobin (2011) recorded parasitism by C. concinnata that varied between 1.6% and 11.9%, Timms and Smith (2011) showed that parasitism by C. concinnata on gypsy moth in Ontario, Canada varied between 2.5% and 5.9% in successive years. In all three of these studies, C. concinnata caused higher larval mortality than any of the four other parasitoid species that had been recorded attacking the larval stage of gypsy moth in earlier studies (Reardon 1976;Williams et al 1992).…”
Section: Effects Of C Concinnata On Gypsy Moth Populationsmentioning
confidence: 96%
“…In addition, existing studies investigating how the diversity of nonā€target insects is affected by defoliator outbreaks and suppression have not addressed whether the impacts vary from local to regional scales (Sample et al , ; Work & McCullough, ; Rastall et al , ; Boulton et al , ; Timms & Smith, ). Previous studies have focused on diversity within individual localities (sites) but, as is recognized within community ecology (Whittaker, ), regional (Ī³) diversity results from a combination of both local ( Ī± ) diversity and variation in diversity across space ( Ī² ā€diversity).…”
Section: Introductionmentioning
confidence: 99%